1995
DOI: 10.1074/jbc.270.46.27880
|View full text |Cite
|
Sign up to set email alerts
|

Ras Is Not Required for the Interleukin 3-induced Proliferation of a Mouse Pro-B Cell Line, BaF3

Abstract: It has been demonstrated that Ras is involved in in-. Furthermore, the activation of fos gene promoter following IL-3 stimulation was almost completely abolished when Ras(S17N) was induced. Under these conditions, Ras(S17N) exhibited no inhibitory effect on IL-3-dependent proliferation assessed by the increase of cell numbers and a mitochondrial enzyme activity. The results indicate that Ras-dependent pathways, including the Raf/MAPK/Fos pathway, are dispensable for IL-3-induced growth stimulation. When BaF3 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
63
2

Year Published

1996
1996
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 58 publications
7
63
2
Order By: Relevance
“…Of these, the Ras pathway has been well characterized by the use of an array of the receptor mutants and dominant-negative as well as activated mutants of Ras (Kinoshita et al, 1995;Terada et al, 1995). In BaF3 cells, overexpression of dominant-negative Ras did not impair IL-3-dependent growth under conditions where the Raf/ extracellular signal-regulated kinase (ERK) cascade was diminished, raising the notion that Ras is not crucial for cell proliferation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, the Ras pathway has been well characterized by the use of an array of the receptor mutants and dominant-negative as well as activated mutants of Ras (Kinoshita et al, 1995;Terada et al, 1995). In BaF3 cells, overexpression of dominant-negative Ras did not impair IL-3-dependent growth under conditions where the Raf/ extracellular signal-regulated kinase (ERK) cascade was diminished, raising the notion that Ras is not crucial for cell proliferation .…”
Section: Introductionmentioning
confidence: 99%
“…In BaF3 cells, overexpression of dominant-negative Ras did not impair IL-3-dependent growth under conditions where the Raf/ extracellular signal-regulated kinase (ERK) cascade was diminished, raising the notion that Ras is not crucial for cell proliferation . Instead, Ras is implicated in the prevention of cell death as evidenced by an anti-apoptotic e ect of an ectopically expressed active Ras mutant (Kinoshita et al, 1995;Terada et al, 1995). For this function, PI3-K and ERK were identi®ed as important players downstream of Ras .…”
Section: Introductionmentioning
confidence: 99%
“…These results are supported by the ®ndings that expression of constitutively activated Ras or Raf protect from apoptosis induced by growth factor deprivation and p53 (Canman et al, 1995;Lin et al, 1995a;Kinoshita et al, 1995;Cleveland et al, 1994;Terada et al, 1995). Paradoxically, introduction of a dominant-negative Ras protein failed to promote apoptosis in BaF3 cells cultured in IL-3, arguing against Ras-dependent pathways playing a role in anti-apoptosis signaling in these cells (Terada et al, 1995). Recently, the Janus kinase (Jak) family of kinases, which regulate the Stat (Signal transducers and activators of transcription) family of transcription factors, have received attention as important mediators of cytokine signal transduction.…”
Section: Discussionmentioning
confidence: 73%
“…Activation of the Ras/Raf/MAP kinase pathway has also been implicated in survival signaling mediated by several di erent receptor systems, including those activated by cytokines (Kinoshita et al, 1995;Xia et al, 1995). These results are supported by the ®ndings that expression of constitutively activated Ras or Raf protect from apoptosis induced by growth factor deprivation and p53 (Canman et al, 1995;Lin et al, 1995a;Kinoshita et al, 1995;Cleveland et al, 1994;Terada et al, 1995). Paradoxically, introduction of a dominant-negative Ras protein failed to promote apoptosis in BaF3 cells cultured in IL-3, arguing against Ras-dependent pathways playing a role in anti-apoptosis signaling in these cells (Terada et al, 1995).…”
Section: Discussionmentioning
confidence: 88%
“…Further analysis using the tyrosine kinase inhibitor genistein and the MEK1 inhibitor, PD98059, indicated that activation of either the genistein sensitive signaling or the PD98059 sensitive signaling pathways of bc may be su cient to suppress apoptosis (Liu et al, 1999c). Consistent with this notion, it was reported that constitutive active Ras prevents DNA fragmentation induced by factor depletion but that dominant negative Ras failed to block the anti-DNA fragmentation activity or the cell viability induced by IL-3 (Okuda et al, 1994;Terada et al, 1995). These observations indicate that activation of the Ras/MAPK pathway by IL-3/GM-CSF is dispensable for the anti-apoptosis activity of GM-CSF while forced activation of this pathway can rescue cells from factor depletion induced apoptosis.…”
Section: Introductionmentioning
confidence: 95%